What Makes the Life of Stressed Plants a Little Easier? Defense Mechanisms against Adverse Conditions - Muszyńska, Ewa; Dziurka, Kinga; Labudda, Mateusz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Plants show different strategies for coping with stress factors. They develop various types of adaptations to avoid the stressor or to activate defense reactions consisting of damage repair and running alternative metabolic pathways. This Special Issue, "What Makes the Life of Stressed Plants a Little Easier? Defense Mechanisms against Adverse Conditions", contains several original articles that deal with such changes that occur at the level of the transcriptome, proteome, and metabolome, as well as structural adaptations in response to a stress factor. It also provides four review articles on drought stress, metal stress, various abiotic stress responses of cultivated beet, and crosstalk between Ca2+ and other regulators in stress signaling.